Determinants of Officiers Militancy: The Case of the National Union of Teachers in Israël - Dolan, Shimon (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1979)
This study reports on an empirical investigation aimed at enhancing the understanding of the ways in which personal and structural factors contribute to attitudinal militancy of officers of a national union of teachers. The study sought to assess the relationship between selected personal at tributes and selected structural characteristics in the union, and their effect on attitudinal militancy.